A Review on Intranasal Insulin Drug Potential Effect on Alzheimer Disease in Type 2 Diabetic Patients - Hanin Al-Towairqi, Abrar Alshanqiti, Rahaf Alsaadi, Yosra Alhindi (Pakistan Journal of Medical & Health Sciences, 2022)
Massive evidence is available regarding the connection between Alzheimer disease and Diabetes Mellitus and their common pathological mechanisms, including impaired brain insulin signaling that can contribute to alteration of protein, glucose and lipid metabolism, chronic inflammation, oxidative stress, and mitochondrial dysfunction. However, the evidence is limited regarding the exploration of potential disease modifying therapies, which can prevent from progressive neuronal death, leading to cognitive impairment, which is the devastating end stage of Alzheimer. To enhance brain insulin, function a recent approach to mitigate Alzheimer symptoms is to centrally administer insulin is through intranasal delivery. To avoid the blood-brain barrier, a large amount of insulin can be administered intravenously (intranasally) by injecting it directly into the nasal cavity (BBB). In healthy adults, intranasal insulin has been shown to alter CNS measurements. Type 2 diabetics may benefit from an intranasal insulin medication that slows the progression of Alzheimer's disease, according to a new study.